TIPOLOGI KITAB-KITAB HADIS: TELAAH KLASIFIKASI DAN KARAKTERISTIK DALAM TRADISI ULAMA - kamaludin kamaludin (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2026)
This article aims to examine the typology of hadith collections based on their classification and compilation characteristics in the tradition of Islamic scholars. The study employs a qualitative-descriptive approach with library research methods, analyzing primary sources such as classical hadith books and scholarly commentaries, as well as contemporary academic references. The findings indicate that hadith books exhibit diverse typologies, including al-Jami‘, al-Sunan, al-Musnad, al-Muwattha‘, and al-Mustadrak. Each type features unique objectives, compilation methods, and structural formats tailored to the scholarly needs of their respective periods. This typological analysis reflects the richness and depth of the Islamic scholarly tradition in preserving and transmitting the Prophet Muhammad’s ﷺ sayings. The study aims to contribute to the advancement of contemporary hadith scholarship.